સમીકરણ ${9^x} - {2^{x + {1 \over 2}}} = {2^{x + {3 \over 2}}} - {3^{2x - 1}}$ નો ઉકેલ મેળવો.

  • A

    ${\log _9}(9/\sqrt 8 )$

  • B

    ${\log _{\left( {9/2} \right)}}(9/\sqrt 8 )$

  • C

    ${\log _e}(9/\sqrt 8 )$

  • D

    એકપણ નહીં

Similar Questions

જો $x + \sqrt {({x^2} + 1)} = a,$ તો $x =$

$\sqrt {[12 - \sqrt {(68 + 48\sqrt 2 )} ]} = $

જો $x = \sqrt 7 + \sqrt 3 $ અને $xy = 4,$ તો ${x^4} + {y^4}=$

જો $x = {2^{1/3}} - {2^{ - 1/3}},$ તો $2{x^3} + 6x = $

${{{{2.3}^{n + 1}} + {{7.3}^{n - 1}}} \over {{3^{n + 2}} - 2{{(1/3)}^{l - n}}}} = $